Effect of non-genetic factors on milk production performance and composition traits in Sahiwal cattle - Kumar, Suchit; Mukherjee, Anupama; Yadav, Alok Kumar; Pathak, Prajwalita; Saleem, Saleem (Indian Journal of Dairy Science, 2020)
The present investigation was carried out on data of first lactation production traits related record of 300 Sahiwal cows for milk production and milk composition traits among them 154 records for protein traits calves during 2000 to 2017 and 2006 to 2013 respectively. The data collected from Record Cell, Animal Genetics and Breeding Division and Livestock Production Management Division of ICAR-National Dairy Research Institutes, Karnal were collected. Least squares analysis was done to study the effect of different non-genetic factors on milk production performance traits. The period of calving was found to be significant on first lactation total milk Yield (FLTMY), first lactation 305days or less fat yield (305DFY), first lactation 305 days or less milk solids-not-fat yield (305DSNFY), first lactation length (LL) and highly significance effect on first lactation 305 days or less milk yield (305DMY). The data collected on various production performance and composition traits do not provide a true reflection of genetic merit of an individual because it is affected by several non-genetic factors. So the needs of adjustment of significant data before estimation of mean performance and genetic parameters are of primary importance. Under present study, least squares analysis was carried out to assess the effect of non-genetic factors, especially the season and period of calving on first lactation production performance traits. Due to difference in feeding management, different culling level and difference in climatic condition.Â  For improving milk production performance traits maintaining good environmental condition, optimum replacement dairy cattle and maintain superior bull for breeding.